Is There Life After ‘Death’ for the Greek Economy? - Alexiou, Constantinos; Nellis, Joseph (International Journal of Economics and Financial Issues, 2013)
The on-going and seemingly endless financial crisis within the European union in conjunction with the austerity measures implemented by a number of member states, have caused a great deal of speculation to emerge regarding the appropriate policy responses needed to put the already derailed economies back on track. In this context, price competitiveness is looked upon as the key factor that has to be positively affected if the conditions for sustainable economic recovery are to be established. We examine the role of a number of key variables such as wage cost, inflation, profit margins and the euro in relation to competitiveness as well as focus on fluctuations in the Greek unit labour costs over time, in comparison with 35 industrialized countries both inside and outside the Eurozone. We address the question: is there a meaningful economic future for the Greek Economy? We find that in relative terms Greek labour costs cannot be held solely responsible for the country’s critical economic situation. We also stress that to lay all the blame at the foot of the Greek workers is wrong and is not supported by empirical evidence. Responsibility must also rest with the corporate sector given that businesses have enjoyed high profit margins overtime. There must be a rebalancing in the distribution of income if the Greek economy is to be pulled out of its crisis. Keywords: Financial crisis; unit labour cost; competitiveness; Greece JEL Classifications: E42; F13; F33